Fabrication of CNTs/MnO2 composite as a wrapping layer for surface modification of Cr-doped LiNi0.5Mn1.5O4 for lithium ion batteries. Issue 91 (16th September 2016) - Zhang, Yu-Hang; Zhao, Qin; Cong, Li-Na; Bao, Sheng-Da; Xie, Hai-Ming; Sun, Li-Qun
Abstract : Cr-doped LiNi0.5 Mn1.5 O4 decorated by a special CNTs/MnO2 wrapping layer shows better electrochemical performance. Abstract : Needle-like MnO2 is deposited on the surface of CNTs using a simple redox reaction and simultaneously forms a special wrapping layer on the surface and among the particles of Cr-doped LiNi0.5 Mn1.5 O4 through an auto-grow process. The CNTs act as a conductive network of electrons and the needle-like MnO2 increases the contact points among the particles and furthermore provides additional Li + diffusion paths. The CNTs/MnO2 composite is also a protective layer to suppress the side reaction between the electrode and the electrolyte. The CNTs/MnO2 -coated, Cr-doped LiNi0.5 Mn1.5 O4 (CNTs/MnO2 –Cr-LNMO) shows superior electrochemical properties, with a high specific capacity and excellent cycling stability at high voltage and high rate.